Rechargeable Co3O4 porous nanoflake carbon nanotube nanocomposite lithium-ion battery anodes with enhanced energy performances1. Issue 58 (25th June 2015) - Qiu, Song; Gu, Hongbo; Lu, Guixia; Liu, Jiurong; Li, Xiaoyu; Fu, Ya; Yan, Xingru; Hu, Chenxi; Guo, Zhanhu
<x xml:space="preserve">Abstract</x> Multi-walled carbon nanotube nanocomposites intertwined with porous Co3O4 nanoflakes serve as lithium-ion battery anode materials with enhanced performances.